If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(-1x + 2) = -3(7x + 2) Reorder the terms: 10(2 + -1x) = -3(7x + 2) (2 * 10 + -1x * 10) = -3(7x + 2) (20 + -10x) = -3(7x + 2) Reorder the terms: 20 + -10x = -3(2 + 7x) 20 + -10x = (2 * -3 + 7x * -3) 20 + -10x = (-6 + -21x) Solving 20 + -10x = -6 + -21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21x' to each side of the equation. 20 + -10x + 21x = -6 + -21x + 21x Combine like terms: -10x + 21x = 11x 20 + 11x = -6 + -21x + 21x Combine like terms: -21x + 21x = 0 20 + 11x = -6 + 0 20 + 11x = -6 Add '-20' to each side of the equation. 20 + -20 + 11x = -6 + -20 Combine like terms: 20 + -20 = 0 0 + 11x = -6 + -20 11x = -6 + -20 Combine like terms: -6 + -20 = -26 11x = -26 Divide each side by '11'. x = -2.363636364 Simplifying x = -2.363636364
| (y-7)=2(x+2) | | 14x+(2-x)=6(2x-1) | | 7(x+5)+3=6(x+5) | | 4v-2=30 | | 40+6=n-3 | | Y-5=4(x+6) | | 2=10c-4(2-9) | | y=-2x^2+16x-34 | | y=-2x^2+16-34 | | 9(x+3)=4x-4 | | 18=9 | | 10y-2y=646 | | -26+x+2=16 | | .5x+5=7+1 | | X+2=4x-4-5x+2 | | 6x-14-4x=28 | | 3h(h+1)=3h^3 | | x^4-4x^3-10x^2+28x-15=0 | | x^2-x+150=180 | | 5x+7=6x-18+3x+1 | | 3x+3=3x-1+2+2x | | 2ex=12 | | 2a^2+6a-8=2 | | 15cm=30cm | | -8x+12+9x=2+x+10 | | 30cm=15cm | | 2v-14=4(v+1) | | 2n+5=13-(-n) | | 0.4x=38 | | 6in=18in | | 5d-8=(3d+2) | | 5x+1x=27+7x |